PELAKSANAAN DISMISSAL PROSEDUR DI PENGADILAN TATA USAHA NEGARA PEKANBARU BERDASARKAN PASAL 62 AYAT (1) UNDANG-UNDANG NOMOR 5 TAHUN 1986 JO UNDANG-UNDANG NOMOR 9 TAHUN 2004 TENTANG PERADILAN TATA USAHA NEGARA - M Alpian; Dodi Haryono; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Proscess dismissal is the examination of any claim by the President of the Court before the case was forwarded to a panel of judges. Dismissal procedure or the Consultative Meeting set in Article 62 of Law No. 5 of 1986 concerning the State Administrative Court. In this consultative meeting President of the Court examine whether a lawsuit lawsuit entry has met the requirements as regulated in Law No. 5 of 1986 concerning the State Administrative Court and whether the mandate of the Administrative court for trial. Therefore, it should be studied simultaneously on the First, Regulation dismissal procedures in the State Administrative Court by Regulation Legislation in Indonesia, the Second, the judges Still Continuing Examination Subject Matter of the Case are not included in the Administrative Dispute.This type of research used in writing this law is the law of sociological research. Population and sample is overall the parties relating to the issues examined in this study, the data source used, primary data, secondary data, and the data tertiary, data collection techniques in this study with interviews and literature study.The results showed that there are two main things that can be inferred. First, Regulation dismissal procedures in the State Administrative Court based on the laws and regulations in Indonesia, that the provisions of Article 62 Paragraph (1) of Law No. 5 of 1985 Jo Law Number 9 of 2004 concerning State Administrative Court governing dismissal procedures or consultative meeting is unclear, because the mechanism or procedure of checking the lawsuit is not regulated in detail, the presiding judge has the authority to carry out inspection of a lawsuit in the consultative meeting and examination preparation. Second. The judges Still Continuing Examination Subject Matter of the Case are not included in Dispute State Administration, the judges should look Evidence Section 100 Paragraph (1) of Law No. 5 of 1986 concerning the State Administrative Court, namely: a letter or writing, expert testimonies , witness statements, confessions of the parties and the knowledge of the judge. First author's suggestion, Article 62 Paragraph (1) No. 5 of 1986 which discusses theprocess of dismissal revised again in order to carry out the detailed process of dismissal referred to in Article 62 of Law No. 5 of 1986 concerning the State Administrative Court.Thus, in the process of dismissal of the lawsuit filed by the individuals and civil agencies clearly understand the functions of the dismissal process, so that individuals and civil legal entity is not harmed. Secondly, To the State Administrative Court to allow the dismissal to be effective. So the lawsuit that has been through the process of dismissal can actually meet the formal requirements and are not repeated occurrence not kewewenang Administrative Courts handle.Keywords: Dismissal Procedures - Of The State Administrative